2001
DOI: 10.1097/00005392-200101000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Metastasis of Renal Cell Carcinoma: Presentation, Treatment and Survival

Abstract: We advocate aggressive surgical resection when possible. Surgical removal of metastatic lesions prolongs survival but radical lymph node dissection is not mandatory. We also recommend careful long-term followup of patients with a history of renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
2
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 14 publications
6
102
2
12
Order By: Relevance
“…Out of all cases of pancreatic-occupying lesions, the reported incidence of pancreatic metastasis is 2-5% (1)(2)(3)(4)(5)7,14). In the present study, pancreatic metastases represented 1.02% of all cases of malignancies encountered in the pancreas.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Out of all cases of pancreatic-occupying lesions, the reported incidence of pancreatic metastasis is 2-5% (1)(2)(3)(4)(5)7,14). In the present study, pancreatic metastases represented 1.02% of all cases of malignancies encountered in the pancreas.…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, the proportion of patients affected by pancreatic metastases is speculated to be significantly higher based on the longer lifespans and improved sensitivity of diagnostic medical examinations. As pancreatic metastases almost always occur in elderly patients and those with later-stage malignancies, certain authors have suggested that the prognosis for pancreatic metastasis is better than primary pancreatic cancer (4,15). Research should be conducted to develop improved diagnostic and treatment techniques for pancreatic metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these patients may suffer from particular complications (such as biliary tree obstruction) due to its complex relation with its surrounding structures, current literature seems to suggest that they tend to have good prognostic indices and have a "slow-burning" course [19]. Real world data seem to suggest that RTK inhibitors can benefit patients across the spectrum of performance status and age although little is known about particular cohorts of patients with rare metastatic sites like the pancreas [20].…”
Section: Introductionmentioning
confidence: 99%